Cell–cell signaling during the Brassicaceae self-incompatibility response. (May 2022) - Abhinandan, Kumar; Sankaranarayanan, Subramanian; Macgregor, Stuart; Goring, Daphne R.; Samuel, Marcus A.
Abstract : Self-incompatibility (SI) is a mechanism that many plant families employ to prevent self-fertilization. In the Brassicaceae, the S- haplotype-specific interaction of the pollen-borne ligand, and a stigma-specific receptor protein kinase triggers a signaling cascade that culminates in the rejection of self-pollen. While the upstream molecular components at the receptor level of the signaling pathway have been extensively studied, the intracellular responses beyond receptor activation were not as well understood. Recent research has uncovered several key molecules and signaling events that operate in concert for the manifestation of the self-incompatible responses in Brassicaceae stigmas. Here, we review the recent discoveries in both the compatible and self-incompatible pathways and provide new perspectives on the early stages of Brassicaceae pollen–pistil interactions. Highlights: Compatibility factors, EXO70A1, GLO1, and PLD⍺1, function at the nexus of the basal compatible pollen response pathway and self-incompatibility pathway. A mitogen-associated protein kinase (MAPK) module renders the stigma receptive to compatible pollen by ensuring plasma membrane localization of EXO70A1. Pollen-derived pollen coat protein (PCP-Bs) controls pollen hydration and germination by reducing reactive oxygen species (ROS) levels in the stigma papillae following pollination. They compete with RALF23/33 peptides for interaction with the ANJEA–FERONIA (ANJ–FER) receptor complex and thereby repress ROS production. ROS production mediated by the FERONIA receptor kinase regulates self-incompatibility responses in Brassica rapa. Autophagy is a newly identified mechanism for regulation of the self-incompatibility (SI) response in arabidopsis ( Arabidopsis thaliana ) . Small noncoding RNAs (sRNAs) and Helitron transposons are pollen-derived factors that modulate self-incompatibility.